2021
DOI: 10.1101/2021.06.14.448456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic autonomic nervous system patterns differentiate human emotions and manifest in resting physiology

Abstract: Whether activity in the autonomic nervous system differs during distinct emotions remains controversial. We obtained continuous multichannel recordings of autonomic nervous system activity in healthy adults during a video-based emotional reactivity task. Dimensionality reduction revealed five principal components in the autonomic time series data, and these modes of covariation differentiated periods of baseline from those of video-viewing. Unsupervised clustering of the principal component time series data un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This further supports the notion that psychophysiological measures need to be modeled over time given they are process-based measures. Future research should explore if more granular analyses are warranted to understand if vagal tone changes occur more frequently than every 5 min in line with research finding changes in other measures of autonomic functioning at smaller time scales (e.g., Golland et al, 2014;Pasquini et al, 2022). Even though 5 min is thought to be the minimum amount of time necessary for an accurate HRV measure, other work finds reliable estimates for shorter time periods (Laborde et al, 2017;Tung et al, 2021).…”
Section: Limitations and Future Workmentioning
confidence: 92%
See 1 more Smart Citation
“…This further supports the notion that psychophysiological measures need to be modeled over time given they are process-based measures. Future research should explore if more granular analyses are warranted to understand if vagal tone changes occur more frequently than every 5 min in line with research finding changes in other measures of autonomic functioning at smaller time scales (e.g., Golland et al, 2014;Pasquini et al, 2022). Even though 5 min is thought to be the minimum amount of time necessary for an accurate HRV measure, other work finds reliable estimates for shorter time periods (Laborde et al, 2017;Tung et al, 2021).…”
Section: Limitations and Future Workmentioning
confidence: 92%
“…Previous research found individual differences in HRV measures over time were due to external task demands and features (Smolders et al, 2012;Obradović and Finch, 2017;Blanck et al, 2019;Smith et al, 2019;Schwarck et al, 2021;Spangler et al, 2021;Tung et al, 2021;Benz et al, 2022), even with very low birth weight neonates (Padhye et al, 2009). Similarly, prior research has shown differences in autonomic activity in response to emotional stimuli when investigated as longitudinal trajectoriesa feature not previously found when the autonomic activity was averaged across trials (e.g., Golland et al, 2014;Pasquini et al, 2022). Thus, autonomic functions including cardiac vagal tone are not likely to remain stable over long periods of time and have been used to measure individual differences in cognitive and emotional regulation.…”
Section: Introductionmentioning
confidence: 92%